A vineyard in my glass - Asher, Gerald (University of California Press, 2011)
Gerald Asher, who served as Gourmet's wine editor for thirty years, has drawn together this selection of his essays, published in Gourmet and elsewhere, for the collective insight they give into why a wine should always be an expression of a place and a time. Guiding the reader through twenty-seven diverse wine regions in France, Italy, Spain, Germany, and California, he shows how every wine worth drinking is a reflection of its terroir--in the broadest sense of that untranslatable word. In evocative reminiscences of wines, winemakers, and the meals he has had with them, he weaves together clim.